Safety of Abatacept in Rheumatoid Arthritis With Serologic Evidence of Past or Present Hepatitis B Virus Infection. Issue 6 (26th May 2016) - Padovan, Melissa; Filippini, Matteo; Tincani, Angela; Lanciano, Elisabetta; Bruschi, Eleonora; Epis, Oscar; Garau, Pietro; Mathieu, Alessandro; Celletti, Eleonora; Giani, Leopoldo; Tomietto, Paola; Atzeni, Fabiola; et al.
Abstract : Objective: Rheumatoid arthritis (RA) with concomitant hepatitis B virus (HBV) infection represents a therapeutic challenge due to the risk of HBV reactivation under immunosuppressive treatment. To date there are few data coming from anecdotal case reports that concern HBV reactivation following treatment with abatacept. This observational retrospective study was aimed to assess the safety profile of abatacept in this particular clinical setting. Methods: Eleven Italian rheumatologic centers provided data from patients with RA and positive HBV serology treated with intravenous abatacept. HBV markers and clinical and laboratory data were checked at followup visits every 3 months. Results: In total, 72 patients were included in the study: 47 inactive carriers, 21 occult carriers, and 4 chronic active carriers for HBV. At baseline all of the patients had normal liver function tests and low or undetectable HBV DNA levels, except for those with chronic active hepatitis. Thirteen patients received prophylaxis with lamivudine, and 4 received treatment with adefovir or tenofovir. At the end of the 24‐month followup period, 49 patients were being treated. Data from 316 followup visits showed that abatacept was safe. No patients experienced reactivation of hepatitis B. Treatment withdrawals (23 patients) were due to lack of efficacy, subject decision/lost at followup, or adverse events not related to HBV infection. Conclusion: Our study provides reassuring data about the safety profile of abatacept in RA with concomitant HBV infection without universal antiviral prophylaxis. Further prospective studies are needed to confirm these preliminary results.